2001
DOI: 10.1161/01.hyp.37.4.1191
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Uterine Perfusion Pressure During Pregnancy in the Rat Is Associated With Increases in Arterial Pressure and Changes in Renal Nitric Oxide

Abstract: Abstract-A reduction in nitric oxide (NO) synthesis has been suggested to play a role in pregnancy-induced hypertension.We have recently reported that normal pregnancy in the rat is associated with significant increases in whole-body NO production and renal protein expression of neuronal and inducible NO synthase. The purpose of this study was to determine whether whole-body and renal NO production is reduced in a rat model of pregnancy-induced hypertension produced by chronically reducing uterine perfusion pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
283
0
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(309 citation statements)
references
References 21 publications
14
283
0
8
Order By: Relevance
“…* P Ͻ 0.05, measurements in tumor necrosis-␣ (TNF-␣; 1,000 pg/ml)-treated vessels are significantly different from corresponding measurements in control TNF-␣ nontreated vessels of virgin and pregnant rats; † P Ͻ 0.05, significantly different from corresponding measurements in endothelium-intact (ϩ Endo) vascular strips. L-NAME, N G -nitro-Larginine methyl ester; ODQ, 1H-[1,2,4]oxadiazolo [4,3]-quinoxalin-1-one. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…* P Ͻ 0.05, measurements in tumor necrosis-␣ (TNF-␣; 1,000 pg/ml)-treated vessels are significantly different from corresponding measurements in control TNF-␣ nontreated vessels of virgin and pregnant rats; † P Ͻ 0.05, significantly different from corresponding measurements in endothelium-intact (ϩ Endo) vascular strips. L-NAME, N G -nitro-Larginine methyl ester; ODQ, 1H-[1,2,4]oxadiazolo [4,3]-quinoxalin-1-one. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing concentrations of ACh, bradykinin, or sodium nitroprusside were added, and the extent of vascular relaxation was measured. In other experiments, nontreated and TNF-␣-treated vascular strips were incubated for 30 min in the presence or the absence of N G -nitro-L-arginine methyl ester (L-NAME, 100 M), to inhibit NOS, or with 1H- [1,2,4]oxadiazolo [4,3]-quinoxalin-1-one (ODQ, 1 M), to inhibit cGMP production in smooth muscle (32,52), and the effects on the Phe-induced contraction and the ACh-induced relaxation of Phe contraction were measured. The concentrations of L-NAME and ODQ were selected based on previous studies, which have shown that these inhibitors are effective and specific at the concentrations used in this preparation (26,52,58,64).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21] Experimental studies in animal models have suggested that a reduction in the uteroplacental perfusion pressure and the ensuing placental ischemia/hypoxia during late pregnancy initiate a cascade of hemodynamic and vascular changes that lead to increased systemic vascular resistance and hypertension. [17][18][19][20][21] For example, studies from our laboratory and others' have demonstrated that reduction in uteroplacental perfusion in pregnant rats results in significant hemodynamic changes and a hypertensive state that closely resembles hypertension of pregnancy in women. 18,20,21 We have also found that the reduction in uteroplacental perfusion pressure in pregnant rats is associated with decreased vascular relaxation and enhanced vascular contraction, suggesting that these vascular changes could contribute to the increased vascular resistance and hypertension of pregnancy.…”
mentioning
confidence: 99%
“…A thin endometrial lining may mirror previous or a current uterine pathology, and with the importance that uterine artery blood flow has on endometrial growth, we could conclude that improving uterine blood flow may facilitate achieving higher pregnancy rates. The significance of nitric oxide (NO) as a modulator of uterine blood flow through the relaxation of vascular smooth muscle by a cyclic guanosine monophosphate (cGMP)-mediated pathway has been studied [8]. Phosphodiesterase (PDE) enzymes also play a role in the NO-CGMP cycle by hydrolyzing cGMP through degrading the phosphodiester bond in these second messenger molecules and so regulating the signal transduction mediated by cGMP.…”
Section: Introductionmentioning
confidence: 99%